The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1097/01.ccx.0000163651.57730.73
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal chest compression-ventilation ratio?

Abstract: The optimal compression-ventilation ratio is still unknown and the best tradeoff between oxygenation and organ perfusion during cardiopulmonary resuscitation is probably different for each patient and scenario. A discrepancy between what is recommended by the current guidelines and the 'real world' of cardiopulmonary resuscitation has resulted in a near flat survival rate from cardiac arrest in the past few years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 69 publications
0
12
0
1
Order By: Relevance
“…Changes to the procedure included the process for locating the pressure point for chest compressions and also a change in the ratio of chest compressions to mouth-to-mouth ventilations to 30:2 [4,5] in order to decrease interruptions in chest compressions and thereby provide more continuous coronary blood flow [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Changes to the procedure included the process for locating the pressure point for chest compressions and also a change in the ratio of chest compressions to mouth-to-mouth ventilations to 30:2 [4,5] in order to decrease interruptions in chest compressions and thereby provide more continuous coronary blood flow [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Studied interpretation of the available evidence [26,[38][39][40][41][42][43][44][45] supports the contention that at least some ventilations should occur during resuscitative efforts from cardiac arrest. Acid-base balance and oxygenation are important factors in survival from states of profound shock [46][47][48].…”
Section: The Benefit Of Ventilationsmentioning
confidence: 73%
“…Several well established laboratories have previously demonstrated that chest compression only CPR can be as effective as chest compressions and rescue breathing during the first 6-12 min of cardiac arrest in animal models [38][39][40][41][42][43]. The persistence of an open airway in these models, allowing for ventilation produced by chest compressions alone or in conjunction with spontaneous gasping, may not reflect physiology in human resuscitation [26,[38][39][40][41][42][43].…”
Section: No Ventilationsmentioning
confidence: 91%
See 1 more Smart Citation
“…While many studies have been performed by different researchers to investigate various hemodynamic and mechanical aspects of the application of chest compressions during CPR [2,7,10,11,14,15,17,[19][20][21][22]25], as of now comparatively few studies have investigated the conditions required to achieve optimum CC performance during CPR [4,5,8,12,24,26]. Most of the previous work in this area has focused on determining the best CC to ventilation ratio during CPR in infants [5,26] and adults [4,12,24]. The optimal CC depth for children was also studied experimentally by Braga et al [8] using computer tomography.…”
Section: Introductionmentioning
confidence: 99%